66‐1: Invited Paper: Fast‐response IPS‐LCDs used in VR applications. Issue 1 (29th May 2019) - Matsushima, Toshiharu; Seki, Kenta; Kimura, Shunichi; Iwakabe, Yasushi; Watanabe, Yoshihiro; Komura, Shinichi; Uchida, Makoto; Nakamura, Takashi
Abstract : We discuss the moving picture characteristics of display devices required for virtual reality head‐mounted displays (VR‐HMDs). We propose a fast response in‐plane switching (IPS) liquid crystal display (LCD) mode, called the short‐range lurch control IPS (SLC‐IPS) LCD mode, for VR‐HMDs based on experimental results of its response properties.